Treatment strategies for adenomyosis before and after introducing USgHIFU in Shenzhen - Yu Dai; Huang-jin Luo; Yan Peng; Weichun Yang; Qiuling Shi; Ping Jin (International Journal of Hyperthermia)
Objective To explore the impact of ultrasound-guided high-intensity focused ultrasound (USgHIFU) on patients with adenomyosis in Shenzhen and the changes in health economics.Design A retrospective observational study.Setting Hospitals.Patients 1093 patients with adenomyosis either treated with surgery or USgHIFU.Intervention(s) Surgical treatment and USgHIFU.Main Outcome Measure(s) Demographic information on the patients including age, education, marital status, job, fertility requirement and clinical characteristics such as fertility history, dysmenorrhea, degree of dysmenorrhea, hypermenorrhea, duration of dysmenorrhea, Numerical Rating Scale and history of cesarean section were recorded.Results The overall trend in the number of patients with adenomyois was increasing after introduction. The average hospital stay of USgHIFU was decreasing year by year, and it was lowest among the three groups with below the total average length of hospitalization. The average cost of patients treated with USgHIFU was decreasing with the total earing for the hospital increasing. Compared to those with USgHIFU, patients selected hysterectomy are older (odds ratio [OR] = 1.17, 95% confidence interval [CI]: 1.13–1.21). However, patients undergoing hysterectomy have fewer symptoms of dysmenorrhea (OR = 0.31, 95% CI: 0.80–1.42) and tend to have lower educational levels. Patients selected adenomyomectomy tended to experience lower levels of dysmenorrhea (OR = 0.76, 95% CI: 0.60–0.93.Conclusion(s) USgHIFU reduces the cost and length of hospitalization for patients with adenomyosis and increases hospital revenue from these patients. It provides a suitable option for women with who have a strong desire to retain their uterus.